The use of conservation biomass feedstocks as potential bioenergy resources in the United Kingdom. (July 2016) - Phillips, D.; Mitchell, E.J.S.; Lea-Langton, A.R.; Parmar, K.R.; Jones, J.M.; Williams, A.
Highlights: Estimated the amount of biomass available from conservation areas in the UK. Examined the combustion properties of the species available. Studied the combustion of wood logs, Reeds and charcoal in a stove. Most of the conservation biomass could be used as a domestic fuel. Abstract: A number of countries have introduced energy policies to reduce the emission of carbon dioxide which, in the case of bio-heat, has resulted in increased use of small wood burning stoves and boilers, particularly in Europe. There are issues surrounding the supply of sustainable wood feedstock, prompting a desire to utilise local biomass resources. This includes biomass generated through the management of natural woodlands in nature reserves and conservation areas. These management practices can also extend to other areas, such as raised bog wildernesses and estuary Reed beds. We term the biomass from this resource as conservation biomass. This study is concerned with the viability of this resource as a fuel within the United Kingdom, and combustion tests were carried out using a small domestic stove. It was concluded that there is as much as 500 kt y −1 that could be used in this way.